IMPLEMENTASI PENDAFTARAN PENDUDUK SEBAGAI UPAYA TERTIB ADMINISTRASI DITINJAU DARI HUKUM ADMINISTRASI NEGARA DI KOTA PALEMBANG (Solusi, 2022)
Population administration is part of the system of state administration, has an important role in government and development of population administration. The problem discussed in this study is how to implement population registration as an effort to orderly administration in terms of State Administrative Law and the provisions of the implementation of population administration services. The approach method used in this research is a normative legal research approach. Normative legal research is an approach method used to determine the legal norms contained in statutory regulations. The results of this study are the implementation of an e-KTP based on a national network as a step in implementing the applicable laws and regulations. The Central Government together with the Regional Government assisted by Implementing Agencies have made optimal efforts in terms of implementing e-KTP which is an administrative order and part of the implementation of State Administrative Law and the provisions for the implementation of population administration services already have a fairly comprehensive basis of statutory provisions. Service systems and procedures have been implemented according to the standard provisions of Law Number 23 of 2006 concerning Population Administration, then the standard of public services refers to Law Number 25 of 2009 concerning Public Services.